Exploitations Familiales de Production Agricole des Cercles de Niono et de Banamba (Mali): Caractérisation et Stratégies de Prise en Charge des Besoins en Rapport Avec L’intervention Pour le Développement Agricole et Rural - Ndiaye, Amadou; Sangaré, Yacouba (European Scientific Journal, ESJ, 2017)
The development of family farming is an important strategic option to support the food needs of the rural and urban populations. This is the reason it has been the subject of several studies which is based on characterization and typology to better orientate agricultural and rural development interventions. This study was conducted to characterize family farm in Mali and to determine the strategies to satisfy the countryâ€™s needs in rapport with the implementation of rural development. In doing this, field data were first collected in the family farms at Niono County (Niger River valley) and the Banamba County. After data collection, it was then analyzed in a systemic way. This analysis helps to characterize the family farm of Mali as a â€œTraditional peasant farmâ€. In Niono County, â€˜peasant family farmâ€™ which ensures its food self-sufficiency is centered on the production unit with an option of diversification. In Banamba County, â€œpeasant family farmâ€™ centered on unity of consumption develops food security strategy through pluri-activity. Thus, despite the intensity of government intervention, particularly in the area of Niger River Valley, malian â€œpeasant family farmgâ€ did not turn into â€œModern family farm businessâ€. In doing this, intervention for agricultural and rural development should move based on its strategies and practices from a sectorial approach to a systemic approach. This passage from the deterministic and holistic paradigm to the systemic and interactionist paradigm, should better redefine agricultural education and agricultural subsidy in relation with the structure of production.